Sales characteristics of Pokémon trading cards: A prospective one-year field study - Johannes Heck; Sarah Schormann; Benjamin Krichevsky; Adrian Groh; Thorben Pape; Sebastian Schröder; Alexander Glahn; Carsten Schumacher; Martin Schulze Westhoff (PLoS ONE, 2026)
Since its inception in North America in 1999, the Pokémon trading card game has become a global phenomenon, combining strategic gameplay with collectible culture. The economic value of Pokémon trading cards, particularly as collector’s items, underscores their significance beyond mere playthings, making them a subject of both academic and commercial interest. In the present study, a convenience sample of 300 Pokémon trading cards were offered on the e-commerce platform eBay between 28 May 2024 and 27 May 2025, with a minimum follow-up period of 3 months per card. All cards were sold nationally in Germany to avoid high shipping costs for international transactions. The aim of the study was to comprehensively analyze sales characteristics of Pokémon trading cards, using both descriptive and inferential statistical techniques including “survival” analyses and Cox regression models. 73.3% (220/300) of the trading cards were sold during the study period, generating a total revenue of 923.60 €. Sales prices showed a markedly skewed distribution, with a median of 1.95 € per trading card. Rare and holofoil cards contributed overproportionately to the total revenue. Uncommon cards exhibited an interesting economic potential due to rapid sales kinetics. Cards from the expansions Team Rocket and Gym Challenge were considerably more popular than Base Set 2 cards, as reflected by shorter “survival” times. The vast majority of buyers were male, but female buyers spent more money per trading card on average. The German federal states Thuringia and Hamburg emerged as Pokémon trading card hubs, with numbers of cards sold and cumulated revenues exceeding expectations based on population sizes.